2011
DOI: 10.2355/isijinternational.51.2012
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium Relationships between Oxide Compounds in MgO–Ti2O3–Al2O3 with Iron at 1873 K and Variations in Stable Oxides with Temperature

Abstract: It is important to determine the equilibrium relationships between the oxide compounds in MgO-Ti2O3-Al2O3 and iron to avoid Al2O3 or MgO·Al2O3 formation and for inclusion control. In this study, the equilibrium relationships between the oxide compounds in MgO-Ti2O3-Al2O3 and molten iron are investigated at 1 873 K. The phase-stability diagrams, which show the equilibrium relationships between the oxide compounds in MgO-Ti2O3-Al2O3 and molten iron, are described. It is also important to know the oxides that new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The systematic studies of Mg deoxidation in Fe 10 mass% Ni have been carried out by Suito et al It was found that complex deoxidation of the Ti followed by strong deoxidant Mg is one of the most promising methods to precisely control the composition, size, and number of deoxidation particles. The thermodynamic calculations of the stability diagram Mg‐Al‐Ti‐O system has also been done by Hono et al and Ren et al…”
Section: Introductionmentioning
confidence: 97%
“…The systematic studies of Mg deoxidation in Fe 10 mass% Ni have been carried out by Suito et al It was found that complex deoxidation of the Ti followed by strong deoxidant Mg is one of the most promising methods to precisely control the composition, size, and number of deoxidation particles. The thermodynamic calculations of the stability diagram Mg‐Al‐Ti‐O system has also been done by Hono et al and Ren et al…”
Section: Introductionmentioning
confidence: 97%
“…[1][2][3][4][5] Inclusions adversely affect the toughness, fatigability and ductility of steel because of their high melting points, high hardness, and brittleness. 1) Oxides inclusions in steel serve as effective sites for the initiation of hydrogen induced cracking (HIC). 2,3) Larger and elongated inclusions such as manganese sulfide (MnS) have a remarkable influence on ductile fractures.…”
Section: Introductionmentioning
confidence: 99%
“…However, more work should be performed to measure the exact value of e Ti Mg due to the huge difference between e Ti Mg ¼ À47:4 [42] and e Ti Mg ¼ À18:4 [37] by Ono et al and e Ti Mg ¼ À 0:64 [61] by Jo et al The formation reaction of Al 2 O 3 in the molten iron is expressed by Eq. [5].…”
Section: B Thermodynamic Calculation Of Mg-al-ti-o Complex Inclusionsmentioning
confidence: 99%